Tailoring the Anodic Hafnium Oxide Morphology Using Different Organic Solvent Electrolytes - Apolinário, A. (2020)
Highly ordered anodic hafnium oxide (AHO) nanoporous or nanotubes were synthesized by electrochemical anodization of Hf foils. The growth of self-ordered AHO was investigated by optimizing a key electrochemical anodization parameter, the solvent-based electrolyte using: Ethylene glycol, dimethyl sulfoxide, formamide and N-methylformamide organic solvents. The electrolyte solvent is here shown to highly affect the morphological properties of the AHO, namely the self-ordering, growth rate and length. As a result, AHO nanoporous and nanotubes arrays were obtained, as well as other different shapes and morphologies, such as nanoneedles, nanoflakes and nanowires-agglomerations. The intrinsic chemical-physical properties of the electrolyte solvents (solvent type, dielectric constant and viscosity) are at the base of the properties that mainly affect the AHO morphology shape, growth rate, final thickness and porosity, for the same anodization voltage and time. We found that the interplay between the dielectric and viscosity constants of the solvent electrolyte is able to tailor the anodic oxide growth from continuous-to-nanoporous-to-nanotubes.